Referencial pedagógico para análise de ambientes virtuais de aprendizagem - Anjos, Rosana Abutakka Vasconcelos dos (2015)
The increasing advancement of Information and Communication Technologies has led to shifts and changes in various social sectors. In the same way, the education sector has been reformulating their practices and reshaping their areas of knowledge, which now also take place in virtual environments. In this sense, the use of Virtual Learning Environments (VLE) is a growing face of this reality, emerging as a resource to be used in the educational process, giving new meaning to new ways and scenarios for learning, and this infers a reflection on the how this resource is analyzed for use in educational settings, in going beyond a purely technical perspective and instrumental analysis and based on pedagogical principles. In general, inquiries in relation to these Virtual Environments focus on the scope of the tools to the detriment of their pedagogical aspects, or say, the educational purposes of VLE are reduced to undertake the analysis of Virtual Environments. Given this, this research aimed to identify pedagogical aspects from the VLE, taking into consideration some existing evaluation models, to then form the Pedagogical Framework for VLE analysis, which intends to support the process of analyzing, understanding and choosing of a VLE. Groups of elements that could be present in VLE to support the educational processes of teaching and learning, are considered pedagogical aspects. This research adopted the basic procedures of qualitative approach, literature and the descriptive exploratory method, which is generally characterized by the research of subjects with little or no previous studies, intending to look for patterns, ideas or hypotheses about the studied area. In this sense, the study demonstrates bibliographical research tied to the collection of pedagogical aspects present in literature which deals with this subject in parallel with the evaluative questions of VLE, along with the gathering of research of a scientific academic nature that shows pedagogical aspects in VLE through evaluation models. This process of investigation resulted in the creation of the Pedagogical Framework for the Analysis of VLE, and also in the organization of a proposal for pedagogical comprehension in Virtual Environments.